2002
DOI: 10.1016/s0092-8674(02)00738-9
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Myc-Induced Apoptosis in β Cells Exposes Multiple Oncogenic Properties of Myc and Triggers Carcinogenic Progression

Abstract: To explore the role of c-Myc in carcinogenesis, we have developed a reversible transgenic model of pancreatic beta cell oncogenesis using a switchable form of the c-Myc protein. Activation of c-Myc in adult, mature beta cells induces uniform beta cell proliferation but is accompanied by overwhelming apoptosis that rapidly erodes beta cell mass. Thus, the oncogenic potential of c-Myc in beta cells is masked by apoptosis. Upon suppression of c-Myc-induced beta cell apoptosis by coexpression of Bcl-x(L), c-Myc tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
582
3
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 582 publications
(616 citation statements)
references
References 41 publications
27
582
3
4
Order By: Relevance
“…This result was further confirmed by the data that downregulation of rSGF29 in K2 cells lowered the rMTA1 and rODC gene expressions, and antisense ODNs against both genes inhibited the colony formation of K2 cells. Recent study has shown that the elevated expression of c-Myc could promote metastasis (Pelengaris et al, 2002). In this study, we demonstrated that downregulation of rSGF29 could reduce tumorigenicity and lung metastasis.…”
Section: Discussionmentioning
confidence: 51%
“…This result was further confirmed by the data that downregulation of rSGF29 in K2 cells lowered the rMTA1 and rODC gene expressions, and antisense ODNs against both genes inhibited the colony formation of K2 cells. Recent study has shown that the elevated expression of c-Myc could promote metastasis (Pelengaris et al, 2002). In this study, we demonstrated that downregulation of rSGF29 could reduce tumorigenicity and lung metastasis.…”
Section: Discussionmentioning
confidence: 51%
“…26,27 On the other hand, overexpression of Bcl-2 and Bcl-XL proteins with known antiapoptotic functions, promotes tumor development in pancreatic beta-cells, in lymphoid cells and in myeloid cells. [28][29][30] In the present study, we addressed the tissue/cell-specific effects of BID in HCC development. We found a profound decrease in HCC development induced by DEN administration, and as early as 48 h after high-dose DEN injection we found a marked decrease in hepatocyte proliferation markers.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in some tissues, such as pancreatic b cells, activation of Myc triggers rapid apoptotic involution of the entire tissue and suppression of Myc-induced apoptosis is sufficient to foster rapid cell expansion and malignant progression. 23 In other tissues, such as skin epidermis, activation of Myc (and, by implication other oncoproteins) implements a transcriptional program for apoptosis but execution of cell death is then suppressed by endogenous survival factors. 11 In all instances, however, restoration or reinforcement of Myc-induced apoptosis offers the potential of a powerful therapeutic strategy that would, moreover, be tumor specific since it relies on the presence of the underlying tumorigenic Myc lesion.…”
Section: Discussionmentioning
confidence: 99%